Life-history aspects of Chrosomus oreas (Mountain Redbelly Dace) in Catawba Creek, Virginia - Dezarai Thompson; Shelby Hargrave; Gregory Morgan; Steven L Powers (Southeastern Fishes Council Proceedings, 2017)
Life-history aspects of Chrosomus oreas, Mountain Redbelly Dace, were identified using specimens collected monthly from Catawba Creek in Roanoke County, Virginia. Chrosomus oreas were found in depths up to 63.3 cm with a modest relationship between abundance and depth. The largest specimen examined was a female 64.68 mm standard length, 4.80 g eviscerated weight, and 36 months of age. The oldest specimens examined were 37 months of age suggesting a maximum lifespan of approximately three years. Spawning appears to occur from April to early July, with a mean of 243 oocytes (SD = 178) up to 1.61 mm diameter in gravid females. Males begin to reach sexual maturity by approximately one year of age and all males appear to be mature by two years of age. Females do not begin to reach sexual maturity until two years of age. The diet of C. oreas appears to be almost exclusively algae and detritus. Food intake largely mimics energetic investment in gonadic mass as it was lowest in August and generally increased until May. Weight of gut contents increases with size of specimen.
Keywords: Cyprinidae; nest associate; James River